Cultural Communication Strategies of Teachers in Shaping the Character of Cageur, Bageur, and Pinter Students in Senior High Schools in Cianjur Regency - Muslim; Muhammad Reza; Jordy Satria Widodo; Yuyus Rustandi; Ratih Siti Aminah (Lembaga Bale Literasi, 2026)
This study aims to analyze the cultural communication strategies used by teachers in shaping the characters of cageur, bageur, and pinter among high school students in Cianjur Regency. The research employs a qualitative approach with a case study method in a public high school that integrates Sundanese cultural values into its character education program. Data were collected through in-depth interviews with teachers, school leaders, and students, classroom and school cultural activity observations, and documentation studies of character education programs and policies. The findings indicate that teachers apply cultural communication strategies through role modeling, the use of Sundanese language and local expressions, culturally relevant narratives aligned with students’ lives, and dialogic and participatory communication in the classroom. These strategies are strengthened by school culture and regional policies that emphasize the philosophies of cageur, bageur, pinter, and Pancawaluya. This facilitates the internalization of healthy living, good morals, and holistic intelligence among students. The study concludes that teachers act as cultural communicators and character-building agents who bridge Sundanese local wisdom with the demands of 21st-century education.